Konstradiksi Hak Asasi Mantan Narapidana Korupsi Dan Pencabutan Hak Oleh Putusan Pengadilan - Riskiyanti Riskiyanti; Sopyan Resmana Adiarsa (Peneliti.net, 2022)
The rule of law is a state in which the human rights of every citizen are guaranteed by the state. 'Every citizen' here means anyone who is an Indonesian citizen regardless of social status. Human rights are guaranteed in Law no. 39 of 1999 which consists of CHAPTER XI and 106 Articles which explain the rights granted and recognized by the state for every citizen. But in practice, there are the rights of former corrupt convicts that are revoked by the high court. One of the rights revoked is political rights, where they cannot participate in political life. This means that they cannot run for the legislature and do not have the right to be elected.